The Validity of Investor Sentiment Proxies - Chan, Felix; Durand, Robert; Khuu, Joyce; Smales, Lee (WILEY, 2017)
© 2016 International Review of Finance Ltd. Behavioral finance research relies on proxies for unobservable phenomena. Different proxies for the same underlying phenomena should be correlated (formal proof of this proposition is presented in this letter). This letter examines proxies for an unobservable variable, sentiment. We utilize a well-known methodology to construct text-based sentiment proxies and compare these with metrics from Baker and Wurgler. We find that they are not correlated. At least one, but perhaps all, of these are not valid proxies of sentiment.